MicroRNA-17-5p and MicroRNA-130b-3p Promote Radioresistance of Glioma Stem Cells by Targeting PTEN/AKT/HIF-1α Pathway-Controlled Phosphopentose Metabolism - Tao Xie; Yu-Hao Ding; Jun Dong; Xi-An Fu (Analytical Cellular Pathology)
Background. The radioresistance of glioma stem cells (GSCs) is related to some microRNAs (miRs) generated by radiation. This study aimed to investigate the effects of miR-17-5p and miR-130b-3p on the radiosensitivity of GSCs. Methods. miR-17-5p and miR-130b-3p expressions in SU3 and SU3-5R cells were determined. SU3 cells transfected with miR-17-5p or miR-130b-3p mimics or inhibitors were used to determine cell viability after irradiation as well as to examine changes of supernatant glucose, intracellular glucose 6-phosphate dehydrogenase (G6PDH), 6-phosphogluconate dehydrogenase (6-PGDH), reduced nicotinamide adenine dinucleotide phosphate (NADPH), reduced glutathione (GSH), glutathione peroxidase (GSH-Px), phosphatase and tensin homolog (PTEN), hypoxia-inducible factor-1α (HIF-1α), glucose transporter (GLUT)-1/3, protein kinase B (AKT), and p-AKT levels. The target gene of the two miRs was verified by luciferase reporter gene assay. Results. miR-17-5p and miR-130b-3p expressions in the radiation-resistant SU3-5R cells or 8 Gy irradiation-treated SU3 cells were high. After transfection of SU3 cells with miR-17-5p or miR-130b-3p mimics, cell viability, intracellular HIF-1α, GLUT-1/3, AKT, and p-AKT protein expressions, and intracellular G6PDH, 6-PGDH, NADPH, GSH-Px, and GSH levels were high, whereas intracellular PTEN expression and supernatant glucose were low. The opposite effects were also observed in the two miR inhibitors-transfected SU3 cells. Further study confirmed that miR-17-5p or miR-130b-3p could directly bind with the PTEN. Conclusion. Radiation-induced miR-17-5p and miR-130b-3p might cause the radioresistance of GSCs, and the mechanisms were associated with the enhancement of antioxidant production, which was from the increments of AKT/HIF-1α signaling pathway-controlled glucose transmembrane transport and phosphopentose metabolism by targeting PTEN.